Characterization of adult patients with a diagnosis of migraine and osmophobia: the osmograine study - Benítez-Martínez, Brenda; Cantillo-Martínez, Marlon X.; Santoya, Sandra Riveros; Proaños, Nadia; Mejia, Fidel Sobrino (Headache Medicine, 2024)
IntroductionOsmophobia is associated with a greater intensity of the headache, a more significant presence of affective symptoms, and the appearance of cutaneous allodynia.ObjectivesTo determine the sociodemographic and clinical characteristics of patients with episodic and chronic migraine associated with osmophobia.MethodsA cross-sectional analytical observational study, 100 patients were included.Results65% of the patients presented osmophobia, 64.6% of patients with osmophobia had chronic migraine, and 35.4% had episodic migraine without statistically significant differences p=0.120. Regarding the clinical characteristics, pulsatile pain was the most frequent in 49%, and severe intensity was present in 81%. Statistically significantrelationships were found between osmophobia and photophobia [(95.4 vs 77.1]; p=0.005), phonophobia ([96.9 vs 74.3); p=0.001) and allodynia ([75.4 vs 45.7); p=0.002). The that become chronic factors were more frequent in the group with osmophobia, in which an association with the excessive use of analgesics ([43.8%vs. 22.9%]; p=0.029) and a history of anxiety and depression ([32.8% vs. 14.3%]; p=0.045). In the multivariate model, the variables associated with osmophobia with statistically significant differences were photophobia, allodynia, and botulinum toxin application.ConclusionsIn this first study of osmophobia in migraine in Colombia, osmophobia is a frequent symptom in patients with chronic migraine; it has related to markers of central sensitization; it is also related to that become chronic factors and the use of botulinum toxin. Therefore, it is likely that osmophobia can predict the risk of that factor, causing the disease to become chronic.